Equations of state from individual one-dimensional Bose gases. (23rd November 2018) - Salces-Carcoba, F; Billington, C J; Putra, A; Yue, Y; Sugawa, S; Spielman, I B
Abstract: We trap individual 1D Bose gases and obtain the associated equation of state by combining calibrated confining potentials with in situ density profiles. Our observations agree well with the exact Yang–Yang 1D thermodynamic solutions under the local density approximation. We find that our final 1D system undergoes inefficient evaporative cooling that decreases the absolute temperature, but monotonically reduces a degeneracy parameter.